2015
DOI: 10.1038/srep15485
|View full text |Cite
|
Sign up to set email alerts
|

Early aggregation preceding the nucleation of insulin amyloid fibrils as monitored by small angle X-ray scattering

Abstract: The nucleation event of amyloid fibrils is one of the most crucial processes that dictate the timing and rate of the pathology of diseases; however, information regarding how protein molecules associate to produce fibril nuclei is currently limited. In order to explore this issue in more detail, we performed time-resolved small angle X-ray scattering (SAXS) measurements on insulin fibrillation, in combination with additional multidirectional analyses of thioflavin T fluorescence, FTIR spectroscopy, light scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 59 publications
1
63
0
Order By: Relevance
“…Furthermore, several techniques including ion mobility-mass spectrometry 10 , ESR 12 , time-lapse solid-state NMR 11 , and the development of methodology using hybrid peptides 33 or a latent fluorophore 34 recently revealed the successful conformational conversion of aggregates to β-sheet-rich fibrils. Previous finding also showed that aggregates convert to mature amyloid fibrils in parallel with their mutual association 35 , which may also be categorized as the NCC mechanism in a broad context.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, several techniques including ion mobility-mass spectrometry 10 , ESR 12 , time-lapse solid-state NMR 11 , and the development of methodology using hybrid peptides 33 or a latent fluorophore 34 recently revealed the successful conformational conversion of aggregates to β-sheet-rich fibrils. Previous finding also showed that aggregates convert to mature amyloid fibrils in parallel with their mutual association 35 , which may also be categorized as the NCC mechanism in a broad context.…”
Section: Discussionmentioning
confidence: 90%
“…This figure also represents that, in parallel with the typical templated assembly of monomers (top right panel), the oligomer species undergoes conformational conversion upon association with preformed nuclei in the step of elongation, a discussion of which is beyond the scope of this review were further investigated by time-resolved SAXS measurements combined with thioflavin T fluorescence, Fouriertransform infrared and light scattering studies. It was revealed that insulin molecules associated into rod-like prefibrillar intermediates in the very early time range of the reaction, and that after their further coalescing to form larger clusters, a conformational conversion towards mature amyloid fibrils occurred (Chatani et al 2015) (Fig. 4).…”
Section: Evidence For the Structural Conversion Of Oligomer-like Aggrmentioning
confidence: 99%
“…In the case of the two-step nucleation mechanism of crystals, the feature of prenucleation clusters is often depicted as highly condensed and liquid-like particles of solutes, inside of which the formation of crystalline nucleus would be facilitated by increasing chances of interatomic or intermolecular interactions (Erdemir et al 2009;Vekilov and Vorontsova 2014). Chatani et al (2014Chatani et al ( , 2015. In this reaction, rod-like shaped prefibrillar intermediates having a partial β-sheet structure (gray regions) are initially formed.…”
Section: Roles Of Precursors In the Formation Of Amyloid Nucleimentioning
confidence: 99%
“…Small-angle neutron scattering (SANS) has been successfully used to analyse static protein aggregate samples [28][29][30], but has been somewhat overlooked by general reviews of techniques for analysing protein aggregation. Particular advantages include probing structures over a range of length scales and minimal beam damage to samples.…”
Section: Introductionmentioning
confidence: 99%